2019
DOI: 10.1021/acssuschemeng.8b06001
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Based Mesoporous Filter Decorated with Silver Nanoparticles for Water Purification

Abstract: Wood is a versatile raw material valued highly for its abundance, low cost, biocompatibility, and natural composition. It has drawn increasing interest for its uses in green electronics, biological devices, and energy storage. Meanwhile, its potential application in water purification has not been adequately explored. This study reports the development of a wood-based filter decorated with silver nanoparticles (Ag NPs) and its application for water purification. X-ray photoelectron spectroscopy (XPS), scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…31,32 The number of micropores in the material may be lower than the minimum value, and mainly mesopores and macropores were found in wood. 33…”
Section: Resultsmentioning
confidence: 99%
“…31,32 The number of micropores in the material may be lower than the minimum value, and mainly mesopores and macropores were found in wood. 33…”
Section: Resultsmentioning
confidence: 99%
“…The contaminant removal ability of xylem filters could be improved further due to fouling (Supplementary Note 10 ), by stacking filters or using other approaches. Use of silver nanoparticles in xylem to enhance the removal of bacteria and methylene blue (a commonly used industrial dye that causes water pollution) using xylem 10 and chemical modification of xylem surface for copper adsorption has been reported 9 . Incorporating suitable sorbents such as zeolites or ferrous oxide into pre-filtration modules could enhance removal of viruses, arsenic, or other pollutants 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The unique structure of gymnosperm xylem gives rise to two interesting questions: (a) is the xylem a suitable material for water filtration, and (b) if so, how can it be engineered to create practically useful water filters. Previous studies have reported that pit membranes in pine xylem can filter bacteria from deionized water and incorporation of silver nanoparticles in xylem can enhance removal of bacteria 7 , 10 . However, several other material characteristics of xylem that are critical for practical water filtration applications, such as its structural stability over the course of its shelf- and operational life, susceptibility to different foulants present in water, and mechanisms of fouling, remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, radiata pine sapwood was decorated with Ag nanoparticles tested in a later study. [ 56 ] Although the results were less desirable in MB reduction (≈98.5% at an initial concentration of 10 ppm), evenly distributed Ag nanoparticles added the function of bacterial inactivation. Overall the Ag/wood filter achieved 6 and 5.2 orders of removal of Escherichia coli and Staphylococcus aureus , respectively (Figure 4e).…”
Section: Engineered Nanowood For Water and Wastewater Treatment And Ementioning
confidence: 99%